The Role of Instructional Leadership in Enhancing Teacher Performance in Primary Schools - Moses Adeleke Adeoye; Abdulrazak Mohammed; Olawale Abayomi Onikoyi (Al Ibtida: Jurnal Pendidikan Guru MI, 2025)
AbstractThe pursuit of quality education, as highlighted in Sustainable Development Goal 4, underscores the importance of instructional leadership in enhancing teacher performance in primary schools. Despite the literature's affirmation of its significance, context-specific practices in socioeconomically diverse settings have received limited attention. This research explores how instructional leadership influences teacher effectiveness and student outcomes in primary education. A quantitative approach was adopted, using secondary data from peer-reviewed journals, government reports, and educational databases. Correlational analysis supported by descriptive statistics revealed that key practices—vision setting, instructional support, professional development, collaborative culture, data-driven decision-making, and fostering a positive school climate—significantly improve teacher performance. These practices enhance classroom management, teaching methodologies, and student achievement. Findings suggest that instructional leadership tailored to local contexts is essential for teacher growth and equitable learning outcomes. By identifying actionable strategies and aligning them with measurable performance indicators, the research contributes to a deeper appreciation for leadership in resource-constrained environments. The research offers insights for policymakers, school leaders, and practitioners seeking evidence-based approaches to strengthen teacher effectiveness and promote excellence in primary education.Keywords: instructional leadership, teacher performance, student outcomes, primary education, collaborative practices. AbstrakUpaya mencapai pendidikan berkualitas, sebagaimana disoroti dalam Tujuan Pembangunan Berkelanjutan 4, menggarisbawahi pentingnya kepemimpinan instruksional dalam meningkatkan kinerja guru di sekolah dasar. Meskipun literatur menegaskan signifikansinya, praktik-praktik spesifik konteks dalam lingkungan sosial ekonomi yang beragam masih kurang mendapat perhatian. Penelitian ini mengeksplorasi bagaimana kepemimpinan instruksional memengaruhi efektivitas guru dan hasil belajar siswa di pendidikan dasar. Pendekatan kuantitatif diadopsi, menggunakan data sekunder dari jurnal peer-review, laporan pemerintah, dan basis data pendidikan. Analisis korelasional yang didukung oleh statistik deskriptif mengungkapkan bahwa praktik-praktik utama—penetapan visi, dukungan instruksional, pengembangan profesional, budaya kolaboratif, pengambilan keputusan berbasis data, dan pembinaan iklim sekolah yang positif—secara signifikan meningkatkan kinerja guru. Praktik-praktik ini meningkatkan manajemen kelas, metodologi pengajaran, dan prestasi siswa. Temuan menunjukkan bahwa kepemimpinan instruksional yang disesuaikan dengan konteks lokal sangat penting bagi pertumbuhan guru dan hasil belajar yang merata. Dengan mengidentifikasi strategi yang dapat ditindaklanjuti dan menyelaraskannya dengan indikator kinerja yang terukur, penelitian ini berkontribusi pada apresiasi yang lebih mendalam terhadap kepemimpinan di lingkungan dengan keterbatasan sumber daya. Penelitian ini menawarkan wawasan bagi para pembuat kebijakan, pemimpin sekolah, dan praktisi yang mencari pendekatan berbasis bukti untuk memperkuat efektivitas guru dan meningkatkan keunggulan dalam pendidikan dasar.Kata kunci: kepemimpinan pembelajaran, kinerja guru, hasil belajar siswa, pendidikan dasar, praktik kolaboratif.